Pendampingan Kegiatan Himaprodi Ekonomi Syariah Berbagi Kasih kepada Anak Yatim Panti Asuhan Tunas Bangsa di Denpasar - Kusjuniati Kusjuniati; Novena Ade Fredyarini Soedjiwo; Yudin Citriadin; Ella Pujianingsih (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Carrying out accompaniment by sharing during the month of Ramadan is an activity conducted by the Sharia Economics Student Association of STAI Denpasar Bali as a form of compassion and a Muslim obligation to share blessings with the needy, as well as to serve the community by addressing one of the needs of orphans at the Tunas Bangsa Washliyah orphanage. The orphans at the orphanage require assistance and loving care as a form of attention and motivation in their daily lives. Therefore, STAI Denpasar students implement accompaniment through a strategy of observation, organization, and activities, followed by an evaluation to understand the response of the orphans and stakeholders who participated in meeting their needs. As a result of the accompaniment, the orphans feel motivated by the attention from the surrounding community, fostering a sense of togetherness, a spirit of sharing, and promoting STAI Denpasar Bali's concern for others.